Real-Time Detection of Lines and Grids By PClines and Other Approaches - Herout, Adam; Dubská, Markéta; Havel, Jiří (SpringerBriefs in Computer Science, 2013)
This text provides a survey of the latest research into the Hough transform for line detection and its contemporary developments. Written with students in mind, this work can serve as a condensed textbook and as a reference for practitioners working in computer vision. The text also presents an overview and detailed elaboration of recent research related to PClines - a line parameterization based on parallel coordinates. A detailed analysis of the concept is given, including implementation details and measurements. One chapter discusses the detection of chessboard-like patterns, and sets of parallel lines and lines coincident with one (vanishing) point - a topic with many applications, such as 2D barcodes, aerial images, and architecture recognition. The work summarizes recent research in the field, and analyses new advances achieved using the PClines parameterization.